2017
DOI: 10.1155/2017/7359095
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Induced Microseizures, Orofacial Dyskinesia, and Speech Dysfluency in an Adolescent with Treatment Resistant Early Onset Schizophrenia on Concurrent Lithium Therapy

Abstract: Clozapine is an atypical antipsychotic used in the treatment of refractory schizophrenia. It has a well-known side effect profile, including agranulocytosis, decreased seizure threshold, and tardive dyskinesia. In addition, numerous case reports have described clozapine-induced stuttering in adults. However, there has been only one previous case report describing it in the adolescent population. In addition, concurrent lithium therapy has been shown to enhance the neurotoxic effects of antipsychotics and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…[8] A few studies on clozapine-induced stuttering suggest an association between the stuttering and a seizure-like activity in EEG and improvement with antiepileptics. [9] However, our patient did not have any seizures clinically or electrophysiologically, which was also the case with many other cases reported earlier. [2] Hence, the exact mechanism needs further systematic evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…[8] A few studies on clozapine-induced stuttering suggest an association between the stuttering and a seizure-like activity in EEG and improvement with antiepileptics. [9] However, our patient did not have any seizures clinically or electrophysiologically, which was also the case with many other cases reported earlier. [2] Hence, the exact mechanism needs further systematic evaluation.…”
Section: Discussionsupporting
confidence: 90%
“… 412 While it is overall considered to be safe, concomitant treatment with clozapine and lithium can markedly decrease the seizure threshold. 151 , 417 , 418 …”
Section: Discontinuation and Re-challenge Of Clozapinementioning
confidence: 99%
“…Regarding the other likely mechanisms of clozapine-induced stuttering, it has been suggested that stuttering may be a manifestation of seizure. Clozapine-induced stuttering was associated with seizure or EEG abnormalities without typical symptoms of seizure in nine out of 30 case reports[ 12 , 25 , 59 , 60 , 62 - 66 ], and stuttering was significantly improved or completely relieved by addition of sodium valproate and the dose reduction of clozapine in five cases[ 12 , 59 , 62 , 64 , 66 ]. In the other four cases[ 25 , 60 , 63 , 65 ], anticonvulsant drugs were not tried, but discontinuation or dose reduction of clozapine resulted in complete relief of stuttering in three cases[ 60 , 63 , 65 ].…”
Section: Clozapine-induced Stutteringmentioning
confidence: 99%
“…After the addition of sodium valproate, the patient had no seizure, but stuttering did not improve. It is worth mentioning that three cases had stuttering with both movement disorders and EEG abnormalities[ 60 , 62 , 63 ], which may demonstrate that some movement disorders induced by clozapine may be due to the epileptiform activity in the brain rather than EPS.…”
Section: Clozapine-induced Stutteringmentioning
confidence: 99%